(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Congenital myopia is a particular form of refractive error which develops prenatally. The reported incidence of myopia in newborns has varied widely, ranging from 6–15% to 25–50%. In the vast majority of cases, myopia in newborns is a transient refractive myopia due to an increased refractive power of the lens, low effect of cycloplegics on the immature ciliary muscle, and some mismatch between some anatomical and optical parameters of refraction. In congenital myopia, there are the blurred out-of-focus images of fixated objects on the foveal and macular regions of the retina, which disrupts normal development both of visual acuity and all central vision functions and structures. Congenital myopia is often associated with amblyopia, which requires specific and durable treatment options. Therefore, timely diagnosis is required to differentiate between the two conditions. Purpose: To compare visual function parameters before and after pleoptic and orthoptic treatment in congenital myopia alone without versus congenital myopia complicated by amblyopia. Materials and Methods: Eighteen children (36 eyes; Group 1) with congenital myopia alone and 11 children (20 eyes; Group 2) with congenital myopia complicated by amblyopia, aged 5 to 12 years underwent an eye examination before and after treatment. Contrast sensitivity was measured using the advanced Bausch & Lomb charts (2013), and color thresholds were measured using the charts we have developed previously (Patent of Ukraine for the Utility Model №114,858 issued 01.2017, “Method for measuring color thresholds in young children”). Treatments used included appropriate optical correction of the refractive error, training of accommodation, pleoptic treatment (illumination of the macula with or without the use of color filters; phosphene stimulation; magnetic stimulation using ATOS apparatus; laser stimulation using LAST and RADUGA apparatuses); computer-assisted treatment; light and color stimulation using ASO and Rucheiok apparatuses; CAM stimulation; and physical therapy (electrophoresis using Aloe vera extract with ascorbic acid; massage of the cervical spine). Results: After treatment, mean visual acuity improved significantly from 0.87±0.15 to 0.9±0.1 in Group 1, and from 0.19±0.15 to 0.37±0.3 in Group 2 (p < 0.05). In addition, Lang II random-dot test and Titmus stereo fly test demonstrated that the stereovision improved in children with amblyopia (Group 2). Moreover, the time till the occurrence of stereo effect improved from 6.6±3.0 sec to 5.33±3.2 sec in Group 1 (p < 0.05). Furthermore, contrast sensitivity increased from 2.04±0.5 points to 2.22±0.5 points in Group 1, and did not change from baseline (1.1±0.7 points) in Group 2. Improvements in red, yellow, blue and green thresholds in Group 2 were more substantial than those in Group 1, and improvement in yellow threshold in Group 2 (p = 0.03) and those in red and blue thresholds in Group 1 were statistically significant. Conclusion: Our pleoptic and orthoptic treatment substantially improved visual acuity and improved stereovision both in patients with congenital myopia and in those with congenital myopia complicated by amblyopia. The two groups, however, demonstrated different changes in contrast sensitivity and color perception. The findings indicate that administration of any concomitant therapy for myopia should depend on the presence of amblyopia, and warrant further research on this subject.